Reservoir Correction for the Central and North Kuril Islands in North Pacific Context. Issue 2 (16th November 2017) - Fitzhugh, Ben; Brown, William A
Abstract: We present new marine reservoir ΔR correction terms for the central and northern Kuril Islands. We estimate ΔR from a series of archaeological charcoal-shell pairs from two archaeological sites using standard calibration procedures and Monte Carlo simulation. The combined ΔR estimate for all paired samples for the Kuril samples is 508±127 yr. In the context of available North Pacific Rim ΔR estimates, the new Kuril data support the interpretation of a well-mixed, 14 C-depleted North Pacific Subarctic Gyre. For the broader subarctic North Pacific region, a ΔR estimate in the range of 440±127 yr is a reasonable correction for any coastal marine shell date, and may be applied to fish and marine mammal dates for taxa known to reside within these waters throughout their life-histories. This generalization fails as one moves south from Hokkaido along the East Asian coast. There, well-equilibrated subtropical water minimize the ΔR offset.